The Shepard-Risset Glissando: Music that Moves You - Mursic, Rebecca A.; Riecke, Bernhard E.; Apthorp, Deborah; Palmisano, Stephen (Experimental Brain Research, 2017)
Sounds are thought to contribute to perceptions of self-motion, often via higher-level, cognitive mechanisms. This study examined whether illusory self-motion (i.e. vection) could be induced by auditory metaphorical motion stimulation (without providing any spatialized or low-level sensory information consistent with self-motion). Five different types of auditory stimuli were presented in mono to our 20 blindfolded, stationary participants (via a loud speaker array): (1) an ascending Shepard-Risset glissando; (2) a descending Shepard-Risset glissando; (3) a combined Shepard-Risset glissando; (4) a combined-adjusted (loudness-controlled) Shepard-Risset glissando; and (5) a white-noise control stimulus. We found that auditory vection was consistently induced by all four Shepard-Risset Glissandi compared to the white-noise control. This metaphorical auditory vection appeared similar in strength to the vection induced by the visual reference stimulus simulating vertical self-motion. Replicating past visual vection findings, we also found that individual differences in postural instability appeared to significantly predict auditory vection strength ratings. These findings are consistent with the notion that auditory contributions to self-motion perception may be predominantly due to higher-level cognitive factors.
Keywords: Riecke; Riecke_2017; deborah-apthorp; journalPaper; rebecca-mursic; stephen-palmisano; vection